2009
DOI: 10.1042/bc20080213
|View full text |Cite
|
Sign up to set email alerts
|

Two new miR‐16 targets: caprin‐1 and HMGA1, proteins implicated in cell proliferation

Abstract: Background information. miRNAs (microRNAs) are a class of non-coding RNAs that inhibit gene expression by binding to recognition elements, mainly in the 3 UTR (untranslated region) of mRNA. A single miRNA can target several hundred mRNAs, leading to a complex metabolic network. miR-16 (miRNA-16), located on chromosome 13q14, is involved in cell proliferation and apoptosis regulation; it may interfere with either oncogenic or tumour suppressor pathways, and is implicated in leukaemogenesis. These data prompted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 38 publications
(65 reference statements)
4
54
0
1
Order By: Relevance
“…Moreover, it is noteworthy that these five miRNAs were associated by the web system to 57 cellular processes, including those in which HMGA proteins have been previously demonstrated to be involved, such as cell proliferation, differentiation, DNA-repair, chromatin modification and regulation of transcription (Fusco and Fedele, 2007;. The direct targeting of HMGA1 by miR-16 (Kaddar et al, 2009), and of HMGA2 by Let-7a (Lee and Dutta, 2007) and miR196ab (De Martino et al, 2009a) was previously reported. Moreover, previous studies showed that miR-26a regulates HMGA2 expression (Lee et al, 2011).…”
Section: Identification Of Hmga-targeting Mirnasmentioning
confidence: 99%
“…Moreover, it is noteworthy that these five miRNAs were associated by the web system to 57 cellular processes, including those in which HMGA proteins have been previously demonstrated to be involved, such as cell proliferation, differentiation, DNA-repair, chromatin modification and regulation of transcription (Fusco and Fedele, 2007;. The direct targeting of HMGA1 by miR-16 (Kaddar et al, 2009), and of HMGA2 by Let-7a (Lee and Dutta, 2007) and miR196ab (De Martino et al, 2009a) was previously reported. Moreover, previous studies showed that miR-26a regulates HMGA2 expression (Lee et al, 2011).…”
Section: Identification Of Hmga-targeting Mirnasmentioning
confidence: 99%
“…Loading equality was assessed by Ponceau red staining analysis and quantification of b-actin or a non-specific protein band (Wang et al, 2005;Kaddar et al, 2009). Quantifications were carried out by densitometric analysis using Kodak 1D Image Analysis Software (Sigma) as previously described (Baghdassarian et al, 1998).…”
Section: Western Blotmentioning
confidence: 99%
“…The half-life of the CDK1 protein was calculated according to the formula: T½ ¼ 0.3t/log(D1/D2), where D1 and D2 correspond to the protein levels at two different times and t is the corresponding interval of time microRNA quantification and microRNA arrays The total RNA was isolated as previously described. The expression levels of reference gene RNU48 as well as mature miR-16, miR-410 and miR-650 were analyzed as previously described (Kaddar et al, 2009) using TaqMan MicroRNA Assays (Applied Biosystems) by RT-qPCR, performed with the Applied Biosystems 7900 Sequence Detection system according to the manufacturer's instructions. According to the RT-PCR efficiency, 15 ng of total RNA was used for RNU48, miR-16 and miR-650 expression assays, whereas 50 ng was used for miR-410 (Supplementary Figure 5).…”
mentioning
confidence: 99%
“…Caprin-1 mRNA is a target of the microRNAs miR-223 and miR-16 (Kaddar et al, 2009;Gong et al, 2013). In a study on the expression of Caprin-1 and miR-223 in several breast cancer cells and normal breast cells, miR-223 expression levels were significantly lower in cancer cells than in normal cells, while Caprin-1 expression was higher in cancer cells than in normal cells (Gong et al, 2013).…”
Section: Introductionmentioning
confidence: 99%